Metformin Enhances Autophagy and Normalizes Mitochondrial Function to Alleviate Aging-Associated Inflammation - Bharath, Leena P.; Agrawal, Madhur; McCambridge, Grace; Nicholas, Dequina A.; Hasturk, Hatice; Liu, Jing; Jiang, Kai; Liu, Rui; Guo, Zhenheng; Deeney, Jude; Apovian, Caroline M.; Snyder-Cappione, Jennifer; et al. (Cell metabolism, 2020)
Age is a non-modifiable risk factor for the inflammation that underlies age-associated diseases; thus, anti-inflammaging drugs hold promise for increasing health span. Cytokine profiling and bioinformatic analyses showed that Th17 cytokine production differentiates CD4+ T cells from lean, normoglycemic older and younger subjects, and mimics a diabetes-associated Th17 profile. T cells from older compared to younger subjects also had defects in autophagy and mitochondrial bioenergetics that associate with redox imbalance. Metformin ameliorated the Th17 inflammaging profile by increasing autophagy and improving mitochondrial bioenergetics. By contrast, autophagy-targeting siRNA disrupted redox balance in T cells from young subjects and activated the Th17 profile by activating the Th17 master regulator, STAT3, which in turn bound IL-17A and F promoters. Mitophagy-targeting siRNA failed to activate the Th17 profile. We conclude that metformin improves autophagy and mitochondrial function largely in parallel to ameliorate a newly defined inflammaging profile that echoes inflammation in diabetes. [Display omitted] •CD4+ T cells from healthy older people preferentially produce a Th17 profile•Autophagy, but not mitophagy, knockdown activates a Th17 profile in “young” cells•Mitochondrial ROS is needed, but not sufficient, for a Th17 profile in “young” cells•Metformin improves autophagy and mitochondria in parallel to decrease inflammaging We uncovered a dominant Th17 inflammaging profile made by CD4+ T cells. Knockdown of autophagy in T cells from young subjects activates this profile. In vitro metformin improves autophagy and mitochondrial function in parallel to ameliorate Th17 inflammaging. Oral metformin intervention improves T cell autophagy in people, indicating potential use for age-associated inflammation.